PENINGKATAN PEMAHAMAN IMUNOHEMATOLOGI BAGI PETUGAS BANK DARAH RUMAH SAKIT MELALUI PELATIHAN PELAYANAN DARAH - Ariani, Resti; KY Astuti, Anna; Puspita, Rina; Pratomo Setyo, Hendro; D Nanar, Dea (LPPM POLBITRADA, 2025)
Training in blood service focused on immunohematology understanding for Blood Bank Hospital (BDRS) personnel plays a crucial role in ensuring blood transfusion safety. This study aims to enhance the knowledge of BDRS staff regarding the fundamental concepts of immunohematology, including antigens, antibodies, and antigen-antibody interactions that impact successful blood matching. This training was conducted using pre-test and post-test methods to assess participants' understanding before and after the session held at the PMI Semarang. Evaluation results indicate a significant improvement in the staff's comprehension of proper blood matching and transfusion reaction management. This training proves that a deeper understanding of immunohematology is essential for minimizing the risks of fatal transfusion reactions and improving the quality of blood services in hospitals. Therefore, this training is crucial for staff responsible for blood management in hospitals to enhance patient safety and medical service efficiency.